Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Samara University - International Livestock Research Institute; Samara University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Samara University. On March 11, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Muhammad Usman Darasa, President of Debark University.